Plate-to-Layer Bi(2)MoO(6)/MXene-Heterostructured Anode for Lithium-Ion Batteries - Zhang, Peng (Nanomicro Lett, 2019)
Bi(2)MoO(6) is a potentially promising anode material for lithium-ion batteries (LIBs) on account of its high theoretical capacity coupled with low desertion potential. Due to low conductivity and large volume expansion/contraction during charge/discharge cycling of Bi(2)MoO(6), effective modification is indispensable to address these issues. In this study, a plate-to-layer Bi(2)MoO(6)/Ti(3)C(2)T(x) (MXene) heterostructure is proposed by electrostatic assembling positive-charged Bi(2)MoO(6) nanoplates on negative-charged MXene nanosheets. MXene nanosheets in the heterostructure act as a highly conductive substrate to load and anchor the Bi(2)MoO(6) nanoplates, so as to improve electronic conductivity and structural stability. When the mass ratio of MXene is optimized to 30%, the Bi(2)MoO(6)/MXene heterostructure exhibits high specific capacities of 692 mAh g(−1) at 100 mA g(−1) after 200 cycles and 545.1 mAh g(−1) with 99.6% coulombic efficiency at 1 A g(−1) after 1000 cycles. The results provide not only a high-performance lithium storage material, but also an effective strategy that could address the intrinsic issues of various transition metal oxides by anchoring them on MXene nanosheets to form heterostructures and use as anode materials for LIBs. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40820-019-0312-y) contains supplementary material, which is available to authorized users.